Economic creativity development through training in organic fertilizer production - Endah Ratna Arumi; Muhammad Haidar; Muhammad Fauzi; Aldhysma Tresna Jati; Fajar Aulia Rahman; Iza Azizah Rizki Aulia (Community Empowerment, 2022)
Sugihmas Village is one of the villages in the Grabag subdistrict where the majority of residents are farmers and ranchers who are members of the Association of Farmers Groups (Gapoktan). This activity attempts to recycle agricultural waste and livestock waste into organic fertilizer in order to boost agricultural production and improve livestock health. The approach of problem solving is accomplished through socialization and production of liquid fertilizer, as well as through training and mentoring in the creation of liquid fertilizer. Along with liquid organic fertilizer, this activity produces dry organic fertilizer.